The City, The Body and The Mind: Interwoven Symbiosis of Nature, People and Architecture - Nyoni, Mandla (School of Architecture, Planning and Geomatics, 2023)
Beyond having an impression on identity, architecture and buildings share a symbiotic relationship in form of providing shelter to the human body. This thesis explores enhancing social fabric through the exploration of the interwoven symbiotic tectonics of the community's culture, their identity and architecture; guided by the understanding of emplaced embodied care. The thesis is formulated as architectural investigations dedicated to exploring roles of architecture in nurturing, sheltering, and reflecting the identity of the communities. Thus, the approach is to challenge how buildings combine the community's customs, traditions and needs with architectural work; leading to the argument that, such initiatives have the common purpose of encouraging the community to have an impact on their built environment and the society and ultimately enhancing social fabric. Even though a synthesis of theory, context, brief and technology this dissertation will expand on the field of architecture through critical reinterpretation of the community's culture and rituals to reimagine an appropriate platform that exhibit the concepts of constructed imagery, personal environment, and social communication in the form of a Iziko Community Life Centre dedicated for Abstract “We are our choices.” This interpretation of the famous saying by the 20th-century existentialist and philosopher Jean-Paul Sartre when he claimed that “existence precedes essence” (Sartre, 38) is one of the often discussed positions towards definition of being. This leads to an understanding that the impression of who we are is defined by the choices that we make daily; these conscious and subconscious choices have an impression on our personality, perceptions, lifestyle, and feelings, conceiving what we can transcend. Mostly our identity is perceived through how we look like and where we come from, commonly through the way we look and live. Sustainable Building Technologies in disaster relief and emergency response in the disaster prone informal community of Imizamo Yethu, Cape Town I am passionate about people, especially those in communities. I believe there is a need to attend to strong social needs with very practical and noncomplex architectural solutions. This thesis presents a platform where I will able to build on my interest in the continued debate on how to make urban environments more equitable and inclusive through the adaptation and reimagination of both public and private spaces. This also aligns with my further personal focus which involves exploring strategies to implementing realistic and progressive solutions to the challenges of environmental and social sustainability and building technologies. I feel the need to practice in authentic, inclusive architecture to assist to upgrade and integrate existing communities while protecting and preserving their identities and culture. My focus is to navigate the complex structures set up in these communities with ultimately focusing in community architecture and the impact it has on the daily living of the general population of South Africa.